2017
DOI: 10.1159/000480703
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival in Patients with Advanced Intrahepatic Cholangiocarcinoma Treated with Gemcitabine plus Cisplatin as First-Line Treatment

Abstract: Objectives: Intrahepatic cholangiocarcinoma (ICC) is a rare type of liver cancer. No clinically useful prognostic factors have been reported for patients with advanced ICC. In the present study, we aimed to evaluate the clinical prognostic factors of patients with advanced ICC receiving gemcitabine plus cisplatin combination therapy (GC) as standard first-line chemotherapy. Methods: A retrospective analysis was performed of the data of patients with ICC treated at our institution from March 2011 to January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Elevated serum LDH has been reported to be associated with chemo-resistance to several anticancer-drugs such as paclitaxel, cetuximab and gemcitabine [2729]. Therefore, consistent with previous reports to the previous studies [12, 18, 19, 30], our study also suggested that elevated serum LDH might be associated with a worse OS in patients with advanced BTC receiving GC therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Elevated serum LDH has been reported to be associated with chemo-resistance to several anticancer-drugs such as paclitaxel, cetuximab and gemcitabine [2729]. Therefore, consistent with previous reports to the previous studies [12, 18, 19, 30], our study also suggested that elevated serum LDH might be associated with a worse OS in patients with advanced BTC receiving GC therapy.…”
Section: Discussionsupporting
confidence: 92%
“…However, from the few studies conducted until date, no predictors of the OS have been identified yet. In addition, few prognostic indexes have been constructed and few validation studies of the prognostic index have been conducted [812]. The purpose of this study, therefore, was to identify and then conduct the prognostic index of OS, and validate it, in patients with advanced BTC receiving GC as first-line chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the location of the primary tumour and the sites of advanced BTC were the suggested prognostic factors, although they did not achieve statistical significance [20]. Ishimoto et al reported 77 patients with pure iCCA and observed that lactate dehydrogenase (LDH), C-reactive protein (CRP), and CEA levels were significantly associated with OS in the multivariate analysis [21]. Suzuki et al analysed 307 patients and identified poor ECOG performance status, elevated serum LDH, and elevated NLR as independent unfavourable prognostic factors [22].…”
Section: Discussionmentioning
confidence: 99%
“…While surgical techniques have expanded in recent years, allowing for curative approaches even for advanced Klatskin tumors applying procedures such as associating liver partition and portal vein ligation (ALPPS) and portal vein embolization (PVE) with subsequent extended liver resection, intrahepatic cholangiocarcinoma can rarely be resected in a curative manner [16,17]. Moreover, biliary tract cancer shows poor response rates to systemic chemotherapy, with overall survival previously reported for gemcitabine monotherapy of 8.1 months and gemcitabine plus cisplatin of 11.7 months [5]; 13.8 months for intrahepatic cholangiocarcinoma [18] and 16.2 months for hepatocholangiocarcinoma [19]. A recent post-hoc analysis of three large clinical trials on advanced ICC showed survival rates of 16.7 months following 3 to 6 months of chemotherapy, which likely reflects improved patient selection and improvements in chemotherapy regimens [6].…”
Section: Discussionmentioning
confidence: 99%